KEBIJAKAN PENGHAPUSAN VERIFIKASI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DALAM PENDAFTARAN HAK ATAS TANAH DI KOTA PADANG - Tri Mardhi Jaya (LPPM Universitas Ekasakti Padang, 2019)
Circular of the Head of the National Land Agency of the Republic of Indonesia Number 5/SE/IV/2013, no longer requires verification of proof of payment of BPHTB payments by the relevant agency, so that contrary to Padang City Regional Regulation Number 1 of 2011 jo. Mayor of Padang Regulation Number 27 of 2016. The question arises, as to the policy arrangement and the legal consequences of the elimination of BPHTB verification in the registration of land rights and registration of the transfer of land rights. Through normative juridical methods, data collection with document studies and interviews, facilitates discussions that are presented through sentence descriptions. The results of the discussion found that the Circular of the Head of the National Land Agency of the Republic of Indonesia Number 5/SE/IV/2013,speed up land services,but contrary to Padang City Regional Regulation Number 1 of 2011 jo. Mayor of Padang Regulation Number 27 of 2016. Therefore, a Joint Circular Letter was issued by the Minister of Home Affairs, Minister of Finance and Head of the Republic of Indonesia National Land Agency.